2010
DOI: 10.1007/s00466-010-0491-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional crack growth with hp-generalized finite element and face offsetting methods

Abstract: A coupling between the hp-version of the generalized finite element method (hp-GFEM) and the face offsetting method (FOM) for crack growth simulations is presented. In the proposed GFEM, adaptive surface meshes composed of triangles are utilized to explicitly represent complex three-dimensional (3-D) crack surfaces. By applying the hp-GFEM at each crack growth step, high-order approximations on locally refined meshes are automatically created in complex 3-D domains while preserving the aspect ratio of elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 70 publications
(147 reference statements)
0
57
0
1
Order By: Relevance
“…As a consequence, a sufficiently fine mesh must be used around the crack front to achieve acceptable accuracy. In the hp-adaptive GFEM presented in [44][45][46] mesh refinement and enrichment are done in the global discretization of a problem, in the same spirit as in the standard FEM. This offsets some of the attractive features of the G/XFEM and adds computational complexity to their implementation in available FEM software.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a sufficiently fine mesh must be used around the crack front to achieve acceptable accuracy. In the hp-adaptive GFEM presented in [44][45][46] mesh refinement and enrichment are done in the global discretization of a problem, in the same spirit as in the standard FEM. This offsets some of the attractive features of the G/XFEM and adds computational complexity to their implementation in available FEM software.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, each crack propagation step may take several hours even on teraflop computers [60]. This paper presents a generalized FEM for crack growth simulations that combines the concept of global-local enrichments introduced in [13,19] with the hp-GFEM for 3-D propagating fractures presented in [48]. The GFEM with global-local enrichments (GFEM gl ) uses a two-scale decomposition of the solution of a fracture mechanics problema smooth coarse-scale component and a singular fine-scale component.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the computing power required to solve this class of problems using existing methodologies can be formidable. Representative methods for three-dimensional crack growth simulations include the standard finite element method (FEM) with remeshing [60], the boundary element method (BEM) [11,36], and the extended [1,8,25,38,57,58] or generalized FEM [18,48]. These methods require the solution of the problem from scratch at each step of a crack growth simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that GFEM has been used successfully in linear elastic fracture mechanics (Areias and Belytschko, 2005;Belytschko, 2001;Duarte et al, 2007;Laborde et al, 2005;Pereira et. al., 2010;Stazi et al, 2003;Tabarraei and Sukumar, 2008).…”
Section: Introductionmentioning
confidence: 99%